2014
DOI: 10.3201/eid2012.141269
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Commercially Available Serologic Diagnostic Tests for Chikungunya Virus

Abstract: Chikungunya virus (CHIKV) is present or emerging in dengue virus–endemic areas. Infections caused by these viruses share some common signs/symptoms, but prognosis, patient care, and persistent symptoms differ. Thus, accurate diagnostic methods are essential for differentiating the infections. We evaluated 4 CHIKV serologic diagnostic tests, 2 of which showed poor sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 14 publications
4
89
1
4
Order By: Relevance
“…Our results indicated that antibody cross-reactivity with reference mouse and rabbit antisera correlated with antigens derived from closely related species within the same antigen serocomplex. Because previous reports suggested that human MAYV serum samples cross-react with CHIKV and RRV antigens in ELISAs (38)(39)(40), another goal of the study presented here was to provide a more detailed analysis of antigen cross-reactivity. In contrast to the results obtained with animal reference antisera, we observed a high degree of specificity for the three human infection groups examined that was primarily based on independently printed E1 and E2 antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that antibody cross-reactivity with reference mouse and rabbit antisera correlated with antigens derived from closely related species within the same antigen serocomplex. Because previous reports suggested that human MAYV serum samples cross-react with CHIKV and RRV antigens in ELISAs (38)(39)(40), another goal of the study presented here was to provide a more detailed analysis of antigen cross-reactivity. In contrast to the results obtained with animal reference antisera, we observed a high degree of specificity for the three human infection groups examined that was primarily based on independently printed E1 and E2 antigens.…”
Section: Discussionmentioning
confidence: 99%
“…IgM antibody levels peak around 3 to 5 weeks and may persist for 3 months (Prat et al, 2014;Labadie et al, 2010). These tests show variable sensitivity and without a more advanced test kit like ELISA being easily available, standardizing the IgM kits in the field becomes difficult.…”
Section: Resultsmentioning
confidence: 99%
“…In acute phase of the febrile illness, most patients may present with similar clinical symptoms and to alleviate, the clinician has to depend on rapid tests. The rapid POC tests are relatively cheaper, widely available, easy to perform, produce faster results but are subjective and can only be used as screening tests due to low specificity (Stacey et al, 2015;Prat et al, 2014). These rapid tests are critical in differentiating Chikungunya from other arboviral infections to institute the correct emergency procedures.…”
Section: Resultsmentioning
confidence: 99%
“…The Euroimmun ELISA, which was used this study, had a specificity of 95% (IgG) and a sensitivity of 88% (IgG). The Euroimmun ELISA test was evaluated as to whether it might detect Mayaro and O'Nyong-Nyong virus and positivity was found (20). Until day 7 after disease onset genome detection by RTPCR is recommended for diagnosis.…”
Section: Discussionmentioning
confidence: 99%